Shalawatan: Pembelajaran Akhlak Kalangan Tradisionalis - Kholid Mawardi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Shalawat is welfare pray and honor greeting to Nabi Muhammad SAW. For traditionalist Muslim, shalawatan or activity to recite shalawat can’t be separated with their paradigm about iman. Shalawatan tradition amongst this community also has purpose to transform noble akhlak (character) of Nabi Muhammad SAW to their daily activity, both in ibadah (ritual) or muamalah (worldly activity).